PEMANFAATAN LIMBAH BOTTOM ASH PENGGANTI AGREGAT HALUS DENGAN TAMBAHAN KAPUR PADA PEMBUATAN PAVING - Mochammad Qomaruddin; Sudarno Sudarno (Reviews in Civil Engineering, 2017)
In connection with the increasing need for paving in the construction world, an effective and economical paving alternative is needed for the community. Paving constituent materials that are still relatively expensive, then the need for other materials that are cheaper without reducing the function and strength of paving itself. Waste is a dangerous material for the environment, such as waste generated PLTU Tanjung Jati B Jepara in the form of waste bottom ash, the result of burning coal that is currently increasingly accumulate because it has not got the right solution. The waste has characteristics such as paving constituents, and in addition to reducing waste that is harmful to the environment. This research is conducted in several stages, starting from the formulation of problem and objectives based on literature problems and reviews, material selection, material testing, object making, object test, data analysis, and conclusion of research result. The results of each test will be analyzed to get the accuracy. The greatest compressive strength results were obtained in the 1PC mix design: 8PS: 0BA: 1KP with a compressive strength of 167,143Kg / cm², and the lowest compressive strength was in the 1PC mix design: 5PS: 3BA: 1KP with a compressive strength of 109,286 Kg / cm². From the results, it can be said that paving in this research can be used in society, although the compressive strength is still not maximal. Keywords: Bottom Ash, Lime, Paving, Strong Press